Dead end in Norvelt - Gantos, Jack. (New York : Farrar Straus Giroux, 2011)
In the historic town of Norvelt, Pennsylvania, Jack Gantos spends the summer of 1962 grounded for various offenses until he is assigned to help an elderly neighbor with a most unusual chore.
Sequoyah Nominee MS 2014
920
Keywords: Human behavior -- Fiction; Old age -- Fiction; Norvelt (Pa.) -- History -- Fiction